2016
DOI: 10.1016/j.chemosphere.2016.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-diketone antibiotics on F1-zebrafish (Danio rerio) based on high throughput miRNA sequencing under exposure to parents

Abstract: The toxicity of β-diketone antibiotics (DKAs), a class of ''pseudo-persistent'' environmental pollutants, to F0-zebrafish (Danio rerio) was investigated using 7-dpf F1-zebrafish miRNA sequencing and bioinformatics analyses. Based on relative expression, 47, 134 and 118 of 193 mature miRNAs were differentially expressed between control vs 6.25 mg/L, control vs 12.5 mg/L and 6.25 vs 12.5 mg/L treatments, respectively. Utilizing three databases, 2523 potential target genes were predicted, and they were assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Sequencing data showed that target genes regulated by high-abundance and positive differentially expressed miRNAs were involved in cancer, hepatitis B, cell cycle, Salmonella infection, metabolism of fatty acid synthesis, etc. (Zheng et al, 2016). However, these results were based on bioinformatics prediction from sequencing data and required further verification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing data showed that target genes regulated by high-abundance and positive differentially expressed miRNAs were involved in cancer, hepatitis B, cell cycle, Salmonella infection, metabolism of fatty acid synthesis, etc. (Zheng et al, 2016). However, these results were based on bioinformatics prediction from sequencing data and required further verification.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA sequencing and bioinformatics analyses for 5-dpf F1zebrafish previously identified a high abundance of positive differentially expressed miRNA-144 and miRNA-125b for each DKA treatment based on the criteria of Log 2 (|fold-change|)≥ 1.0, per million fragments mapped (FPKM)≥ 100 and p < 0.05 (Zheng et al, 2016). To better understand the biological functions of miRNA-144 and miRNA-125b, we predicted their potential target genes using TargetScan software.…”
Section: Bioinformatics Analysesmentioning
confidence: 99%
“…Based on high-throughput screening and histopathological observations, joint DKA exposure on larval and adult zebrafish resulted in abnormal expression of a large number of micro-RNAs; some long non-coding RNAs and their regulating target genes; and a series of physiological changes in tissues and organs, especially those related to the nervous, immune and reproductive systems [ 32 , 112 , 113 , 114 , 115 , 116 ]. For example, the joint FQ and TC exposure induced severe histopathological changes and damage in the zebrafish eye, brain, hepatic and spleen tissues ( Figure 2 ), including vacuolation of interstitial cells, photoreceptor cell cysts, reduced number of neurons, glial cell proliferation, formation of glial scars, hepatic parenchyma vacuolar degeneration and brown metachromatic granules.…”
Section: Effects Of Antibiotic Mixtures In Zebrafishmentioning
confidence: 99%
“…For example, the joint FQ and TC exposure induced severe histopathological changes and damage in the zebrafish eye, brain, hepatic and spleen tissues ( Figure 2 ), including vacuolation of interstitial cells, photoreceptor cell cysts, reduced number of neurons, glial cell proliferation, formation of glial scars, hepatic parenchyma vacuolar degeneration and brown metachromatic granules. On the other hand, the female reproductive system suffered serious damage after chronic exposure to DKAs, as reflected by the increased number of early developmental oocytes, irregular cell distribution, different cellular morphology, decreased yolk granules, cytoplasmic shrinkage and cell lysis in mature oocytes [ 32 ]. Moreover, Wang et al [ 114 ] showed the adverse reproductive effects of β-diketone antibiotics in female zebrafish, along with an effect transfer relation across parents and their offspring.…”
Section: Effects Of Antibiotic Mixtures In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation